2009
DOI: 10.1242/jcs.050963
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiinfection confers resistance against BimS-induced apoptosis by preventing the activation and mitochondrial targeting of pro-apoptotic Bax

Abstract: seen with regard to their conformational changes, the cytosolto-mitochondria targeting and the oligomerization of Bax but not their cellular protein levels. Blockade of Bax and Bak activation was not mediated by the upregulation of antiapoptotic Bcl-2-like proteins following infection. Further, the BH3-mimetic ABT-737 failed to overcome the Toxoplasmaimposed inhibition of Bim S -triggered apoptosis. These results indicate that T. gondii targets activation of pro-apoptotic Bax and Bak to inhibit the apoptogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 48 publications
1
28
0
2
Order By: Relevance
“…1C) and was completely abolished by 1 × 10 8 parasites per ml of cytosolic host cell extract. Thus, T. gondii is able to inhibit activation of the caspase 9-caspase 3 cascade independently of its effect on MOMP 3037.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…1C) and was completely abolished by 1 × 10 8 parasites per ml of cytosolic host cell extract. Thus, T. gondii is able to inhibit activation of the caspase 9-caspase 3 cascade independently of its effect on MOMP 3037.…”
Section: Resultsmentioning
confidence: 96%
“…It was therefore critical to assess whether T. gondii also directly interferes with cytochrome c -induced caspase activation when being confined to its natural intracellular habitat. In order to distinguish between the parasite-mediated inhibition of cytochrome c release from mitochondria as described previously 3037 and the mechanism described herein in infected cells, we measured the caspase 3/7 activity which had been induced in cytosolic extracts from non-infected and T. gondii -infected Jurkat cells after addition of cytochrome c and dATP. The results showed that infection with T. gondii for 24 hours dose-dependently reduced such DEVD-AMC cleavage activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of pathogens have been shown to inhibit host cell apoptosis modulating several survival mechanisms [19][20][21][22][23]. It is well known that apoptosis signaling of a cell can be divided into two pathways, which results into similar outcome, that is, downstream caspase activation and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-apoptotic proteins Bcl-2 and Bcl-X L have been shown to both prevent disruption of mitochondrial physiology and block cytochrome c release from mitochondria (Kroemer 2003;Scorrano and Korsmeyer 2003). A large volume of literature has addressed the mechanisms of apoptosis; and several reports have been reported that T. gondii inhibits the release of cytochrome c from host cell mitochondria (Carmen et al 2006;Goebel et al 2001;Hippe et al 2009). Intracellular pathogens have evolved diverse strategies to avoid destruction by the host immune response.…”
Section: Introductionmentioning
confidence: 99%